Training on Tips and Tricks to Avoid Online Scams in the West Java 1 Electoral District - Surbakti, Feliks Prasepta Sejahtera (Research Collaboration Community (RCC), 2025)
The rise of online fraud has become a pressing issue in today's digital society, affecting individuals and communities across various sectors. This community service initiative aims to increase public awareness and equip participants with effective strategies to avoid falling victim to online scams. The program specifically focuses on addressing common fraud types such as phishing, identity theft, and fraudulent e-commerce activities. The implementation method involved conducting an interactive online training session, leveraging digital platforms to reach a broader audience efficiently. The training included presentations, case studies, and simulations to help participants recognize potential threats and adopt preventive measures. Topics covered ranged from identifying warning signs of fraud, securing personal data, to utilizing cybersecurity tools such as multi-factor authentication and safe browsing practices. The results demonstrated a significant improvement in participants' understanding of online fraud risks and their ability to apply preventive strategies in real-life scenarios. Post-training surveys indicated increased confidence in identifying and avoiding online scams, as well as a commitment to sharing the knowledge with their communities. This initiative highlights the importance of education and technology in combating online fraud and serves as a replicable model for fostering digital safety awareness in diverse communities. The outcomes contribute to creating a more informed and secure digital environment.